Farrell Covington and the limits of style : a novel - Rudnick, Paul (Atria Books, an imprint of Simon & Schuster, Inc, 2023)
"Devastatingly handsome and insanely rich, Farrell Covington is capable of anything and impossible to resist. He's a clear-eyed romantic, an aesthete but not a snob, self-indulgent yet wildly generous. He's the son of one of the country's most powerful and ferociously conservative families, so the world could be his. But when he falls for Nate Reminger, an aspiring writer from a nice Jewish family in Piscataway, New Jersey, the results are passionate and catastrophic. Together, the two embark on a uniquely managed romance that spans half a century. They are inseparable -- except for the many years when they are apart. Moving from the ivy-covered bastion of Yale to New York City, Los Angeles, and eventually all over the world, Farrell and Nate experience the tremendous upheaval and social change of the last fifty years. Taking readers from the freedom of gay life in 1970s Manhattan to the Hollywood closet, from the AIDS epidemic to the joys and perils of getting married and assimilating into mainstream culture, this witty and moving novel shows how the world changes around us while we're busy doing other things. A story of chances lost and found (and sometimes just temporarily misplaced), with an epic reach, it reminds us that there is always the possibility of undiluted, unbridled, unstoppable happiness, if, as Ferrell says, "you know where to look." Style has its limits, but love does not"--Jacket flap.